2022
DOI: 10.1111/eva.13494
|View full text |Cite
|
Sign up to set email alerts
|

The putative maintaining mechanism of gut bacterial ecosystem in giant pandas and its potential application in conservation

Abstract: Animals living in captivity and the wild show differences in the internal structure of their gut microbiomes. Here, we performed a meta‐analysis of the microbial data of about 494 fecal samples obtained from giant pandas (captive and wild giant pandas). Our results show that the modular structures and topological features of the captive giant panda gut microbiome differ from those of the wild populations. The co‐occurrence network of wild giant pandas also contained more nodes and edges, indicating a higher co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 105 publications
2
8
0
Order By: Relevance
“…The composition of microbiota at various taxonomic levels revealed that Firmicutes and Proteobacteria were the predominant phyla, while Streptococcus , Escherichia ‐ shigella , and Clostridium sensu stricto 1 were the major genera. This finding is consistent with previous studies (Cui et al., 2023; Jin et al., 2020; Yan et al., 2021). Although Firmicutes were more abundance in the capable group, there was no significant difference observed between the two groups at the phylum level.…”
Section: Discussionsupporting
confidence: 94%
“…The composition of microbiota at various taxonomic levels revealed that Firmicutes and Proteobacteria were the predominant phyla, while Streptococcus , Escherichia ‐ shigella , and Clostridium sensu stricto 1 were the major genera. This finding is consistent with previous studies (Cui et al., 2023; Jin et al., 2020; Yan et al., 2021). Although Firmicutes were more abundance in the capable group, there was no significant difference observed between the two groups at the phylum level.…”
Section: Discussionsupporting
confidence: 94%
“…Changes in gut microbiota can influence the resistance and pathogenicity of these pathogens ( Bäumler and Sperandio, 2016 ). Captive and wild environments significantly impact the structure and function of gut microbiota in giant pandas ( Guo et al, 2019 ; Yao et al, 2019 ; Tang et al, 2020 ; Hu et al, 2021 ; Cui et al, 2023 ). Furthermore, antimicrobial resistance genes (ARGs) also exhibit different distribution patterns among different geographic populations of giant pandas.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Cui et al demonstrated variances in the topological characteristics of gut microbial networks between captive and wild giant panda populations through network module and keystone species analyses. The findings indicated that the wild giant panda [52] gut microbiome exhibits higher complexity, stability, and resilience to external influences. Cohesion, an innovative method for quantifying connectivity within microbial community networks, has gained widespread acceptance in assessing the relationships and interactions among diverse microorganisms in interdomain ecological networks.…”
Section: Introductionmentioning
confidence: 96%
“…Network analysis, as an excellent microbiome research tool, has been widely employed to gain deeper insights into the intricate relationships that shape the dynamics of microbial communities among different microbial ecosystems [48][49][50][51][52]. Additionally, network analysis assists in identifying keystone species, functional modules, and the importance of ecological niches [4,46,53].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation